Deciphering the impact of endoparasitic infection on immune response and gut microbial composition of Channa punctata - Kumar, Vikash; Roy, Suvra; Parida, Satya Narayan; Bisai, Kampan; Dhar, Souvik; Jana, Asim Kumar; Das, Basanta Kumar (Frontiers in Cellular and Infection Microbiology, 2024)
Intestinal parasitic infections caused by helminths are globally distributed and are a major cause of morbidity worldwide. Parasites may modulate the virulence, gut microbiota diversity and host responses during infection. Despite numerous works, little is known about the complex interaction between parasites and the gut microbiota. In the present study, the complex interplay between parasites and the gut microbiota was investigated. A total of 12 bacterial strains across four major families, including Enterobacteriaceae, Morganellaceae, Flavobacteriaceae, and Pseudomonadaceae, were isolated from Channa punctata, infected with the nematode species Aporcella sp., Axonchium sp., Tylencholaimus mirabilis, and Dioctophyme renale. The findings revealed that nematode infection shaped the fish gut bacterial microbiota and significantly affected their virulence levels. Nematode-infected fish bacterial isolates are more likely to be pathogenic, with elevated hemolytic activity and biofilm formation, causing high fish mortality. In contrast, isolates recovered further from non-parasitised C. punctata were observed to be non-pathogenic and had negligible hemolytic activity and biofilm formation. Antibiogram analysis of the bacterial isolates revealed a disproportionately high percentage of bacteria that were either marginally or multidrug resistant, suggesting that parasitic infection-induced stress modulates the gut microenvironment and enables colonization by antibiotic-resistant strains. This isolation-based study provides an avenue to unravel the influence of parasitic infection on gut bacterial characteristics, which is valuable for understanding the infection mechanism and designing further studies aimed at optimizing treatment strategies. In addition, the cultured isolates can supplement future gut microbiome studies by providing wet lab specimens to compare (meta)genomic information discovered within the gut microenvironment of fish.